2017
DOI: 10.14382/epitoanyag-jsbcm.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Titania-Ceria surfactant assisted sol-gel synthesis and characterization

Abstract: the nanoparticles of titanium dioxide are important in a wide range of applications such as catalysis, environmental remediation and solar energy conversion. While cerium oxide is rareearth oxide material used in the fields of photoluminescence, photosensitive material to uv radiation. Furthermore, research on the synthesis of nanoparticles of titanium dioxide has given rise to different methods such as sol-gel, in solid states, hydrothermal processes, among others. the process of solid state synthesis is most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Torres-Romero et al synthesized Titania-Ceria composite at different sizes through titanium butoxide and cerium nitrate hexahydrate as the precursors. 75 Three years later, Torres-Romero et al 76 indicated that the Titania-Ceria composite presented excellent biocompatibility and delivery efficiency in the drug delivery systems (DDSs) with daunorubicin (DNR) against cancer.…”
Section: Dovepressmentioning
confidence: 99%
“…Torres-Romero et al synthesized Titania-Ceria composite at different sizes through titanium butoxide and cerium nitrate hexahydrate as the precursors. 75 Three years later, Torres-Romero et al 76 indicated that the Titania-Ceria composite presented excellent biocompatibility and delivery efficiency in the drug delivery systems (DDSs) with daunorubicin (DNR) against cancer.…”
Section: Dovepressmentioning
confidence: 99%
“…The sol-gel method has several advantages (Tseng et al, 2010) such as (1) inexpensive and easy to be conducted, (2) lower temperature of preparation, (3) better purity from raw material, (4) better mixing for a system of multi-component, etc. The use of surfactants to assist the synthesis of catalysts via the sol-gel method has been widely carried out (Anderson & Binions, 2014;Galkina, Vinogradov, Agafonov, & Vinogradov, 2011;Phattepur et al, 2019;Torres-Romero, Cajero-Juárez, & Contreras-García, 2017), and the use of tween surfactant has been proven to increase photocatalyst activity and absorption of harmful organic substances (Anderson & Binions, 2014).…”
Section: Introductionmentioning
confidence: 99%